EFFECTS OF ’˜OLEA EUROPEA’ EXTRACT ON VOLUME AND ACIDITY OF CARBACHOL INDUCED GASTRIC SECRETION, LIVER AND KIDNEY FUNCTION IN RABBITS - Jan, Muhammad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Peptic ulcer is mostly produced due to the over production of gastric acid. This study was undertaken to find out the effects of extract from the leaves of medicinal plant Olea europea (which contains documented natural Calcium channel blocker) on volume and acidity of Carbachol induced gastric section. Its effects were also observed on liver and kidney function. Methods: Thirty rabbits of local breed, weighing 1-1.5 kg were used. The animals were kept on fasting for 48 hours, after that the pylorus of each animal was ligated. Carbachol 600 Î¼g/kg body weight and extract from the leaves of Olea europea 500 mg/kg body weight were administered intraperitoneally to group A and B respectively. The extract was also administered in the same dose to group C for 45 days twice daily intraperitoneally to observe its effects on liver and kidney function. Results: The extract reduced the volume, free and total acidity of gastric secretion, which were statistically highly significant when compared with Carbachol (p<0.001). When the differences of means for both the liver and kidney function were compared with that of control group, all these were found statistically non-significant indicating that the extract has no adverse effects on these organs regarding all parameters included in study. Conclusion: Extract can be used effectively and safely in the treatment of hyper gastric acidity conditions and peptic ulcer after evaluation of its effects in human subjects. Keywords: Medical plants, Olea Europea